2023
DOI: 10.1002/admi.202300074
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoassisted Li‐O2 Battery with Ce‐UiO‐66 Metal‐Organic Framework Based Photocathodes

Abstract: Li‐O2 batteries have attracted extensive attention because of their theoretical specific energy equivalent to gasoline, but the poor electrical conductivity of Li2O2 leads to high overpotential, which limits their further development and application. Herein, this work introduces Ce‐UiO‐66, a metal‐organic framework material, as the photocatalyst to reduce the overpotential in the discharging and charging processes. With the simple in situ growth of Ce‐UiO‐66 on carbon cloth as an integrated photocathode, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…When compared with representative, outstanding photo-assisted Li-O 2 batteries in Figure 4e, the Fe-UiO-66 photocathode outperforms by sustaining 500 cycles with higher round-trip efficiency and lower charge/discharge polarization voltage (0.14 V). [7,[13][14]18,36] In comparison to our previously reported Ce-UiO-66 photocathodes, the Fe-UiO-66 photocathodes demonstrated marked enhancement in electrochemical performance, especially for the cycle stability (Figure S22, Supporting Information).…”
Section: Electrochemical Performance and Stabilitymentioning
confidence: 89%
See 1 more Smart Citation
“…When compared with representative, outstanding photo-assisted Li-O 2 batteries in Figure 4e, the Fe-UiO-66 photocathode outperforms by sustaining 500 cycles with higher round-trip efficiency and lower charge/discharge polarization voltage (0.14 V). [7,[13][14]18,36] In comparison to our previously reported Ce-UiO-66 photocathodes, the Fe-UiO-66 photocathodes demonstrated marked enhancement in electrochemical performance, especially for the cycle stability (Figure S22, Supporting Information).…”
Section: Electrochemical Performance and Stabilitymentioning
confidence: 89%
“…[17] Our previous work demonstrated that Li-O 2 batteries with Ce-UiO-66 photocathodes exhibit impressive electrochemical performance under illumination. [18] Ce-UiO-66 extends its light absorption to the visible region due to Ce's low-lying empty 4f orbitals. Notably, targeted single-site MOF node modification is a versatile method for creating stable and active catalysts, capitalizing on noble and transition metals.…”
Section: Introductionmentioning
confidence: 99%